District Heating System Using Heat Pump Installations and CHP - Sit M.L.; Burciu V.I. (Problems of the Regional Energetics)
The article describes the district heating system, in which part of the heat of return water thermal power is used to supply heat to the district heating puThe article describes the district heating system, in which part of the heat of return water thermal power is used to supply heat to the district heating pumps, evaporators heating and hot water. Heat pumps use carbon dioxide as refrigerant. During the transitional period of the year, and the summer heat pump for preparing hot-water supply system uses the heat of the surrounding air. The heat of the ambient air is used in the intermediate heat exchanger between the first and second stages of the heat pump to cool the gas after the first stage of the compressor of the heat pump.